Hadron–quark crossover and hybrid stars with quark core. (1st April 2022) - Li, Bo-Lin; Yan, Yan; Ping, Jia-Lun
Abstract: We construct a new set of hybrid equations of state (EOSs) with a smooth hadron–quark crossover transition from hadronic matter at low densities to strange quark matter at high densities. The hadronic EOS NL3 ωρ is obtained by the relativistic mean field theory, while the strange quark matter EOS is calculated by a quasiparticle model that incorporates the nonperturbative features of quantum chromodynamics. In the transition region, we use a polynomial function to interpolate the pressure as a function of the chemical potential. Most of these hybrid EOSs satisfy the mass constraint of M TOV > 2 M ⊙ and the tidal deformability constraint of Λ1.4 < 800 from GW170817. We find that the presence of strange quark matter at high densities makes the EOS softer. The maximum masses and corresponding radii for the hybrid EOSs are smaller than that for the hadronic EOS NL3 ωρ . For a fixed gravitational mass of 1.4 M ⊙, the central baryonic number densities for the hybrid EOSs are larger than that for the hadronic EOS, and the radii for the hybrid EOSs are smaller than that for the hadronic EOS. This means that the hybrid stars are more compact than the neutron star, and will have smaller tidal deformabilities than that for the neutron star. The radii for hybrid stars are also consistent with the Neutron star Interior Composition Explorer (NICER) analysis of PSR J0030 + 0451 ( M = 1.4 4 − 0.14 + 0.15 M ⊙, R = 13.0 2 − 1.06 + 1.24 km) and PSR J0740 + 6620 ( M = 2.08 ± 0.07 M ⊙, R = 12.35 ± 0.75 km). And the central baryonic number densities for the hybrid EOSs suggest that in the center of the hybrid stars there exists quark–hadron mixed state instead of pure strange quark matter.